Pengaruh Free Cash Flow Dan Pertumbuhan Perusahaan Terhadap Kebijakan Hutang (Studi Kasus Pada Perusahaan LQ 45 Di Bursa Efek Indonesia Tahun 2018-2021) - Muhammad Alif, Atiqullah; Khanifah, Khanifah (Universitas Dian Nuswantoro, 2024)
Debt policy is a policy carried out by a company to obtain funding sources that come from outside the company. It is important for management to make funding decisions for a company, because these decisions can affect the value of a company and thus have an impact on the prosperity of the company owner or share owners. The aim of this research is to examine the influence of free cash flow and company growth on debt policy at LQ 45 Companies on the Indonesia Stock Exchange in 2018-2021. The method used in this research is a quantitative method with purposive sampling technique. The analysis used in this research is descriptive statistical analysis and multiple linear regression analysis. The research results show that partially free cash flow has a positive effect on debt policy because it has a probability value of 0.0004 which is smaller than 0.05, company growth has no effect on debt policy because it has a probability value of 0.5930 which is greater than 0.05. Meanwhile, simultaneously free cash flow and company growth together influence debt policy because they have a probability value of 0.004000 which is smaller than 0.05.